The Relationship between Self-Efficacy and Family Support, Adherence to Taking Hypertension Medication - Abdul Hadi; Parellangi; Amirudin (PT FORMOSA CENDEKIA GLOBAL, 2023)
Hypertension Is a condition where the increase in systolic blood is above the normal limit, which is more than 140 mmHg and diastolic blood pressure is more than 90 mmHg (WHO, 2021). Hypertension or high blood pressure is often referred to as